Relationship between Family Resources and Mother’s Care with Protein Energi Malnutrition (PEM) of Underfive Children - Amaliah Ekasari; Euis Sunarti; Dwi Hastuti Martianto (Media Gizi dan Keluarga, 2000)
The objective of the study is to determine the relationship between family resources and mother's care with PEM status of underfive children. The research was conducted in Kelurahan Cikaret and Desa Rancamaya, Kecamatan Bogor Selatan, Kotamadya Bogor. Samples of the study was 105 PEM children aged 11-59 month whose mothers are primary caregiver. Data was analyzed by using Spearman’s rank test, t-test, and regression analysis. Result showed that there were 54,7 pertcent and 48,1 percent of moderate PEM children in Kelurahan Cikaret and Desa Rancamaya respectively, while severe PEM children were found in Kelurahan Cikaret (1,9%) and Desa Rancamaya (5,8%). Economic resources had significant correlation with mother's care. Non economic resources had significant correlation with mother' care especially sanitation practices, mother's knowledge and educational attainment. Positive correlation was also found between sanitation practices and PEM status (% BB/U). Mother's care were influence by mother's knowledge (a= 0,635), family’s asset (a= 0,362) and mother's educational attainment (a= 0,056). Mother’s care was not significantly related to PEM status of children.Keywords: mother’s care, malnutrition, family resources